(untitled) (Journal of Comparative Social Work, 2023)
This article explores the role of faith in congregational social work. It investigates The Salvation Army (TSA), an international Christian church that provides social services in local communities. TSA’s congregational social work represents a specific case, in which spiritual values dictated by faith and social work principles are explicitly intertwined. In this article, a community of practice (CoP) perspective is used to analyse empirical data from a multiple-case study of TSA congregations. The article concludes that faith can be part of a professional ethos, by adding important values to a holistic understanding of social work